Constraints on the Role of Marine Authigenic Clay Formation in Determining Seawater Lithium Isotope Composition - Charlotte Läuchli; Nestor Gaviria‐Lugo; Anne Bernhardt; Hella Wittmann; Dirk Sachse; Mahyar Mohtadi; Andreas Lückge; Patrick J. Frings (Geochemistry, Geophysics, Geosystems)
Abstract Silicate weathering reactions generate alkalinity that drives carbonate burial in the ocean, ultimately considered to balance solid‐earth CO2 degassing. Because silicate weathering occurs at a climate dependent rate, it provides a negative feedback on long‐term climate evolution that regulates Earth's temperature within a habitable window. Quantifying the effect of silicate weathering on CO2 sequestration is challenging, because an unknown fraction of the alkalinity is consumed by the formation of marine authigenic clays. This process – termed reverse weathering – counteracts the degassing‐weathering feedback loop and retains carbon in the ocean‐atmosphere system. Quantifying reverse weathering is challenging due to the difficulties in detecting and quantifying marine authigenic aluminosilicate clays (MAAC) in marine sediments and distinguishing them from byproducts of alkalinity generating marine (forward) silicate weathering reactions. Here, a comparison of the lithium contents and isotope3 ratios of the clay‐sized fraction of marine and fluvial sediments along Chile suggests that higher lithium contents and 7Li/6Li ratios of marine detrital sediments compared to their fluvial counterparts are diagnostic of the presence of MAACs. The increases in Li content and isotope ratios were used to derive a lithium isotope fractionation of ca. −30‰ associated with the formation of MAACs in sediments derived from continents. Using this new constraint on authigenic clay formation, we reevaluate the global lithium budget and derive a flux of lithium associated with MAAC formation in marine detrital sediments.